Utilisation of subsurface waters for soilless vegetable forcing in the Southern Great Plain region of Hungary - Rácz, I-né (International Journal of Horticultural Science, 2007)
For soilless vegetable production of the Southern Great Plain region in Hungary, there is enough water available, however, the origin and chemical composition of it are decisive from the point of view of practicability. The ground water is everywhere accessible, although its sodium and chloride content is almost always significant, moreover, human pollution may occur (e.g. nitrates and phosphates). A further unfavourable moment is the seasonal variation observed within the area of the same community. The abundant supply of water in the Quaternary strata are located in more than half of the cases within the upper 50 m region. As by the expected changes of the climate, a strategic increment of the importance of subsurface waters is anticipated. Their composition is relatively stable, and the prognoses are reliable for the same settlement. Salt content of the majority of water resources bearing hydrocarbonates is low, however, streaming of the subsurface waters tend to increase their sodium content and to diminish their calcium and magnesium, whereas the pH increases (mainly by ion-exchange). Water quality is decisive not only because of the interaction with the plants but also from the point of view of the distribution of water. Some micro-elements, mainly iron and secondarily manganese may cause problems, therefore, irrigation water ought to be prepared carefully. Production technology should be completed by a technical equipment using aeration for the elimination of ironinfluence of yields on rate of return of investment; (3) the role of increasing of added value content of products. Importance of the utilisation of alternative channels of distribution and the formation of producers’ cooperatives are underlined, being based on calculation of return of investment.